Developing a continuous review (R, Q) policy when the demand during lead-time distributed generalized gamma four-parameters - Ghafour, Karzan Mahdi (CESER Publications, 2016)
This paper focuses on a multi-echelon inventory system under continuous review (R, Q) policy with generalized Gamma four-parameter distribution of demand during lead-time which consist a distribution center and three warehouses that satisfy unlimited retailers. In this paper we were able to reach a new formulation of Economic Order Quantity Q through a mathematical derivation by integration of the probability density function of the demand during lead-time in the inventory total cost function. In addition, the numerical results show the best exploit of the daily production which represents the optimal values of the economic order quantities Q at each echelon and the optimal reorder point R at each installation and echelon. However, this paper is an extend of our previous work which we proved that the demand during lead-time distributed generalized Gamma four-parameters by a simulation model.